The Legitimation Crisis of Mass Education: Habermas's Communicative Rationality as an Analytical Framework for the Erosion of Educational Authority in Late Modernity - Damanik, Fritz Hotman Syahmahita; Sukmana, Oman; Remtula, Jahlan Naftali (IJTIMAIYA: Journal of Social Science and Teaching, 2026)
This article examines the crisis of legitimacy of mass education in late modernity through the perspective of Jürgen Habermas's communicative rationality. The goal is to identify the structural causes of the decline in public trust in educational institutions. Using a critical-interpretive approach that combines theoretical analysis and empirical data, this study identifies three forms of educational colonization: credentialism, standardized measurement, and commercialization. Gallup/Lumina data (2024) shows that trust in higher education has decreased from 57% (2015) to 36% (2024), while Pew Research (2025) notes that 70% of Americans believe higher education is moving in the wrong direction. As a solution, this article offers a Communicative Recovery Framework that includes stages of diagnosis, intervention, and recovery based on Habermasian principles. Future research should test this framework through case studies of institutional reform.